Water-use efficiency for Pinus radiata stands in Chile - Huber J., Anton; Trecaman V., Ramiro (Bosque (Valdivia), 2004)
The water-use efficiency of Pinus radiata, D. Don stands in Chile was determined. The transpiration rate (net evapotranspiration / tree volumetric increase) of selected plantations with different management between the Seventh and Tenth regions of Chile were calculated. Transpiration rate ranged between 241 and 717 m3/ m3. The smaller transpiration rate was registered in zones containing soils with a high water retention, heavy rainfall and little vegetation. The greatest rates of transpiration were determined in the plantations established in zones with less intense precipitation and a high potential evaporation. The transpiration rate was also high in sandy soils because here the trees are exposed to a prolonged water stress which restricts their growth. Precipitation, net precipitation, density of the stand, soil-water retention capacity, summer temperature, and the characteristics of the vegetation explain more than 83.8% (r2) of the variability in the transpiration rate between the studied plantations.